(untitled) (Constructionism Conference Proceedings, 2025)
Integrating maker education into formal schooling systems presents significant challenges due to entrenched educational infrastructures that resist change. This study explores the early stages of infrastructuring maker education through a design-based implementation research (DBIR) approach with a municipal partner. Despite the municipality’s enthusiasm, evidenced by their investments in maker spaces and future plans to expand these efforts, foundational questions emerged regarding the purpose and disciplinary integration of maker education. The onboarding process revealed the need for iterative dialogue, visual tools, and concrete examples to bridge conceptual gaps and align visions. This journey underscores the importance of fostering shared understanding and direction in early stages of the infrastructure process. The findings contribute to the growing literature on infrastructuring for educational change, offering theoretical and practical insights into fostering sustainable, constructionist learning in schools.